What is discussed about eldercare?: A netnography study on a Chinese online community for older adults. Issue 2 (9th April 2020) - Zhao, Dongxiang; Zhang, Qiping; Ma, Feicheng
Abstract : Purpose: The purpose of this paper is to investigate eldercare issues in China through exploring what was discussed about eldercare in a Chinese online community for older adults (OCOA). Design/methodology/approach: Netnography was used to explore eldercare-related online discussion in a Chinese OCOA – LaoYouBang. After a two-month-long online observation, 275 microblogs and 594 comments were collected and analysed qualitatively and quantitatively. Findings: The main findings include as follows: the users involved in an online discussion about eldercare were consist of four categories, namely, elderly user, non-elderly user, advertiser and community administrator. Non-elderly user include the elderly's caregivers and families, young and middle-aged people concerning about eldercare. From 2012 to 2017, eldercare issues gradually became refined and differentiated in China and elderly users' contribution proportion and activeness increased yearly. According to the results of thematic analysis, users' information needs for eldercare included opinion, news, practice, emotion, knowledge and others. In China, some changes have taken place in the public's conceptions of eldercare, embodied in the changes in the public's attention, attitudes and cognition. Changes in user structure and communication patterns in OCOA have also been noted. OCOA plays an important role in eldercare information dissemination and social support exchange and helps to meet the eldercare challenges. Originality/value: This study explored an online community for older adults. This is the first netnography study in the information field on Chinese OCOA. This paper provides new perspectives to explore eldercare issues and OCOA in other regions and cultures and it also provides some suggestions to improve OCOA.